Dasar Pertimbangan Hakim dalam Putusan Bebas Terhadap Pelaku Tindak Pidana Pencurian yang Dilakukan oleh Anak (Putusan Nomor: 9/PID.SUS ANAK/2017/PN.AMP) - I Wayan Jimmy Artana; I Nyoman Putu Budiartha; I Nengah Laba (Jurnal Analogi Hukum, 2019)
Judges are an integral part of the system of rule of law, where the judge is a noble profession and must be free from interpretation in making a decision in order to create legal justice that can be trusted by the community. Based on the description above, there are two formulations of the problem described, namely, how the judge judges in making a case free verdict on the crime of theft committed by the child and any factors considered by the judge. The type of research used in this paper is the type of Normative Law research. By approaching the problem in legislation that is analyzing from the standpoint of legislation and opinions expressed by scholars related to the issues raised. While the approach to the problem used is the legislative and conceptual approach, where the approach is carried out by examining all the laws and regulations concerned with the problem at hand. In this paper, it can be concluded that the judge should have given a verdict lighter than the demands of the public prosecutor, but it is necessary to know whether the decision to return to parents can provide a deterrent effect on the child who is a criminal offender.